2020
DOI: 10.1002/prot.25997
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the N‐acetyltransferase Eis1 from Mycobacterium abscessus reveals the molecular determinants of its incapacity to modify aminoglycosides

Abstract: Enhanced intracellular survival (Eis) proteins belonging to the superfamily of the GCN5related N-acetyltransferases play important functions in mycobacterial pathogenesis. In Mycobacterium tuberculosis, Eis enhances the intracellular survival of the bacilli in macrophages by modulating the host immune response and is capable to chemically modify and inactivate aminoglycosides. In non-tuberculous mycobacteria (NTM), Eis shares similar functions. However, Mycobacterium abscessus, a multi-drug resistant NTM, poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…We next tested substrates suited for numerous GNAT and all possessing primary amines notably histamine, tyramine, spermine, and spermidine (Fig. 1B) [14,40]. This screening identified only spermine and spermidine as substrates of MAB_4324c, with a slightly better apparent activity for spermidine (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next tested substrates suited for numerous GNAT and all possessing primary amines notably histamine, tyramine, spermine, and spermidine (Fig. 1B) [14,40]. This screening identified only spermine and spermidine as substrates of MAB_4324c, with a slightly better apparent activity for spermidine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Eis2 confers high‐level resistance to aminoglycosides in Mab [12–14]. A very close homologue of Eis2, named Eis1, is neither required for intracellular survival [19] nor aminoglycoside resistance, suggesting that it possesses another function that remains to be defined [12,14]. Together, these findings exemplify the need to experimentally address the substrate specificity and biological function of GNAT proteins despite their high homology levels with well‐described homologues.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Eis1 seems to be the closest homologue to Mtb’s Eis by Bidirectional Best Hit (BBH) search ( 91 ). However, it was shown that Mabs’ Eis1 does not modify aminoglycosides, and the basis for this lack of activity was pinpointed to structural reasons, where the active site is too narrow to accommodate large substrates like these antibiotics ( 92 ). Curiously, Mabs Eis2 deletion mutant ( Δeis2 ) was dramatically attenuated in murine macrophages, showing increased ROS levels.…”
Section: Autophagy Inhibitionmentioning
confidence: 99%